The strategy of human resource management of the organization in the context of digitalization of the economy ("Journal "U". Economy. Management. Finance.", 2024)
This article examines human resource management considering the modern requirements of the digital economy, which leads to the adaptation of functional responsibilities and further increase in employee productivity.
Keywords: strategic management; human resources; digital communications; digitalization